2015
DOI: 10.1002/ana.24433
|View full text |Cite
|
Sign up to set email alerts
|

Correcting Neuromuscular Deficits With Gene Therapy in Pompe Disease

Abstract: Objective We have recently reported on the pathology of the neuromuscular junction (NMJ) in Pompe disease, reflecting disruption of neuronal and muscle homeostasis as a result of glycogen accumulation. The aim of this study was to examine how the alteration of NMJ physiology contributes to Pompe disease pathology; we performed molecular, physiological, and histochemical analyses of NMJ-related measures of the tibialis anterior muscles of young-, mid-, and late-stage alpha-glucosidase (GAA)-deficient mice. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 48 publications
4
47
1
Order By: Relevance
“…[37][38][39] Early restoration of enzyme activity to both neural and skeletal muscle tissue is likely to have the greatest effect on physiological outcomes related to treatment strategies as our studies and those of others have demonstrated time-dependent arrests in functional decline after gene therapy. 11,74,75 Reliance upon liver-derived GAA to target neural tissues is dependent upon crosscorrection of neighboring cells through secretion and reuptake of GAA, yet the protein is too large to cross the blood-brain barrier and therefore does not address the neuropathology related to Pompe disease. 6,31 For these reasons, ERT or exclusively hepatic gene transfer would not address glycogen accumulation particularly in the motor neurons involved with ambulation or respiration as evidenced by patients continuing to be wheelchairand ventilator-dependent after long-term treatment of ERT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[37][38][39] Early restoration of enzyme activity to both neural and skeletal muscle tissue is likely to have the greatest effect on physiological outcomes related to treatment strategies as our studies and those of others have demonstrated time-dependent arrests in functional decline after gene therapy. 11,74,75 Reliance upon liver-derived GAA to target neural tissues is dependent upon crosscorrection of neighboring cells through secretion and reuptake of GAA, yet the protein is too large to cross the blood-brain barrier and therefore does not address the neuropathology related to Pompe disease. 6,31 For these reasons, ERT or exclusively hepatic gene transfer would not address glycogen accumulation particularly in the motor neurons involved with ambulation or respiration as evidenced by patients continuing to be wheelchairand ventilator-dependent after long-term treatment of ERT.…”
Section: Discussionmentioning
confidence: 99%
“…11,[42][43][44][45][46][47] In addition, we and others have described the capabilities of AAV-mediated expression of GAA to elicit detrimental immune responses against the transgene. 1,50,55 To address this complication for improved systemic outcomes, we pursued the use of a liver-specific promoter (apolipoprotein Ehepatocyte locus control region-human alpha-1 antitrypsin promoter [LSP]) to drive expression of human codon-optimized GAA (coGAA) for induction of GAA-specific T regs capable of dampening a systemic immune response against GAA.…”
Section: Aav9-lsp-cogaa Selectively Expresses In the Liver After Intrmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, an early therapy appears to be the most effective. 79 First clinical trials of gene transfer treatment in five ventilator-dependent Pompe patients demonstrated acceptable safety outcomes and longer periods of unassisted breathing. 80,81 Genome editing via CRISPR/Cas9 82 is another revolutionary approach that might tremendously change the therapeutic options for Pompe patients by modulating disease-causing alleles.…”
mentioning
confidence: 98%